Pengembangan Sistem Informasi Manajemen Pengelolaan Kearsipan di Lembaga Jaminan Sosial - Dhea Perdana Coenraad; Imam Heryanto; Haris Nurdiansyah; Jimmy Rusjiana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study aims to see to what extent the effectiveness of an information system that has just been implemented in a social security institution where this system is a replacement for the previous system which is considered less effective in managing archives. Based on the results of research and testing, it was found that this new system has a better effectiveness value and a far more optimal level of accuracy in archiving management.